Melatonin alleviates acute spinal cord injury in rats through promoting on progenitor cells proliferation - Bolong Zheng; Dingjun Hao; Hua Guo; Baorong He (Elsevier, 2017)
The previous studies have shown that melatonin is beneficial for nervous system after spinal cord injury (SCI). After SCI, the endogenous neural stem/progenitor cells (eNSPCs) proliferate and differentiate into neurons and glial cells. In the present study, we examined the effect of melatonin on eNSPCs proliferation and differentiation in SCI rat model. SCI rat model was established by dropping a 10 g rod from the height of 25 mm. Then, the rats were randomly divided into the control group, the melatonin treated group, and the G3335 treated group. The Basso-Beattie-Bresnahan locomotor rating scale (BBB scale) was used to evaluate the recovery of locomotor function after SCI. Flow cytometry was used to evaluate eNSPCs proliferation and differentiation. The rats in the melatonin treated group demonstrated significantly faster locomotor function recovery and more eNSPCs proliferation and differentiation. However, these effects were abolished in the G3335 treated group. Melatonin can effectively promote locomotor function recovery via improving eNSPCs proliferation and differentiation after SCI. Keywords: Spinal cord injury, Melatonin, Functional recovery, Endogenous neural stem/progenitor